Workplaces, Low Pay and the Gender Earnings Gap in Britain - Tim Butcher; Karen A. Mumford; Peter N. Smith (Institute of Labor Economics (IZA), 2016)
This study provides a robust assessment of the importance of a number of determinants of the gaps in earnings between the four groups of employees who make up the British workforce; males and females who work full and part-time. The analysis considers the contribution of individual employee characteristics as well as occupation, industry, region and other workplace specific characteristics. The results are compared with previous findings for 2004 (Mumford and Smith, 2009) and with alternative data from the ASHE series for 2004, 2011 and 2015.
Keywords: J01; J70; J78; 330; gender pay gap; low pay